Factor affecting the intention to use digital banking service among University Malaysia Kelantan - Mohamad Aiman Haikal Ismail; Mohamad Azrul Fadzil; Mohamad Nafizal Zaini (2023)
Digital banking is the best thing to happen to humanity. In actuality, technology has not only made banking more convenient, but it is a system that does not require any tools such as paper or pen to implement it. With that, the digital implementation of bank service users makes it easier to deal with transactions, check account balances, and is also more effective if it is used for good, such as in the interweaving of welfare. Banking has always been an information-intensive activity that relies significantly on information technology (IT) to obtain and provide information to all relevant users. IT is not only important in information processing; it also allows banks to differentiate their products and services in the market. As a result, banks have discovered that they must constantly develop and update their information technology in order to retain their clients demanding and knowledgeable. This is to ensure they can provide a convenient, dependable, and beneficial service. Some banks are investing in more bricks and mortar to expand their geographical and market coverage in response to the challenge of expanding and dominating a larger share of the banking market. Others have viewed it as a more revolutionary method to delivering banking services via a new medium known as the internet. The internet is quickly becoming a full-service delivery and distribution medium for consumer-oriented banking products and services. Financial in cyberspace is quickly becoming an alternate channel for providing banking services and goods, thanks to the increasing spread of the internet. The internet is now regarded as a strategic weapon, revolutionizing how banks operate, deliver, and compete with one another, particularly as the competitive advantages of old branch networks erode rapidly. A few decades ago, online shopping was essentially non- existent.